2021
DOI: 10.3390/d13100476
|View full text |Cite
|
Sign up to set email alerts
|

Dead Wood as an Element Enriching Biodiversity of Forest Ecosystems: A Case Study Based on Mites from the Suborder Uropodina (Acari: Parasitiformes)

Abstract: The importance of dead wood in forest ecosystems for the existence of invertebrates has been widely discussed in the literature. The major aim of this study is to test the hypothesis that the presence of dead wood in forests considerably increases the species diversity of Uropodina (Acari: Parasitiformes) communities in a given area. The areas selected for the study are unique from a natural point of view. They are the Białowieża Primeval Forest, Cisy Staropolskie im. Leona Wyczółkowskiego Nature Reserve, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As previous studies have shown, the presence of dead wood increases the overall biodiversity of Uropodina in the examined forest ecosystems by about 40% [7]. This microhabitat is therefore very important for the preservation of Uropodina biodiversity.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…As previous studies have shown, the presence of dead wood increases the overall biodiversity of Uropodina in the examined forest ecosystems by about 40% [7]. This microhabitat is therefore very important for the preservation of Uropodina biodiversity.…”
Section: Discussionmentioning
confidence: 66%
“…Dead wood, along with bird and mammal nests, is one of the microhabitats most frequently colonized by mites from the suborder Uropodina (Acari: Mesostigmata) [1][2][3][4][5][6][7][8]. One of the precursors of the research into Uropodina inhabiting dead wood was Athias-Binche.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until the end of the 1970s, dead wood was removed from nature reserves. Thus, the mites were deprived of one of the most important microenvironments, the presence of which determines the high biodiversity of this group of mites in forests [2,8,9]. Leaving dead trees in the reserve considerably changed the conditions for the functioning of the entire ecosystem, significantly expanding the range of niches for all fauna, including Uropodina.…”
Section: Introductionmentioning
confidence: 99%